Isolamento e tipifícação genotípica de Clostridium Perfringens em frangos de corte. - Alexis de Matos Gomes (2007)
Clostridium perfringens is an anaerobic Gram-positive bacterium which causes gaseous gangrene and enterotoxaemias in humans and domestic animals besides being the primary cause of necrotic enteritis in poultry. Clostridium perfringens strains were isolated 171/250 (68.4%) from the intestinal content of broiler chickens sampled in a slaughterhouse in Pará de Minas, MG. Clostridium perfringens were identified according to Gram staining, lecithinase test on agar TSC-egg yolk, haemolysis in desfibrinated horse blood agar and biochemical tests. Clostridium perfringens strains were classified into five toxigenic types (A -E), which were based on the detection of codifying alfa (cpa), beta (cpb), epsilon (etx) e iota (iA) genes, using multiplex PCR assay for genotyping of the principal and lethal toxins, beta2 toxin (cpb2) and enterotoxin (cpe). Clostridium perfringens strains were isolated in 62/125 (49.60%) from jejunum content and 109/125 (87.20%) strains from ileum. From a total of 62 Clostridium perfringens jejunum isolates obtained 42/62 (67.74%) were type A, 1/62 (1.61%) type A with amplification of products for beta2 toxin gene, 0/62 (0%) type B, 17/62 (27.42%) type C and 1/62 (1.61%) type D. A total of 109 ileum Clostridium perfringens isolates were obtained being 62/109 (56.88%) type A, 3/109 (2.75%) type A with amplification of products for beta2 toxin gene, 1/62 (0.92%) type B, 38/109 (34.86%) type C, 1/109 (0.92%) type D. Clostridium perfringens A (60.82%) and Clostridium perfringens C (32.16%) toxigenic types were the most prevalent types in the analyzed parts of the intestinal content of broiler chickens. Five (2.92%) out of a total of 171 Clostridium perfringens strains were not typified. Clostridium perfringens codifying the iota toxin gen and enterotoxin gene were not detected.